Intelligent integrated predictive model for BTP in lead-zinc sintering process. (13th September 2010) - Wang, Chun-Sheng; Wu, Min
Based on the uncertainty of vertical burning speed and the abnormal sintering states in lead-zinc imperial sintering process, an intelligent integrated predictive model for burning through point (BTP) is proposed. First, a fuzzy T-S predictive model based on the character of piecewise linearity is established to deal with the uncertainty of vertical burning speed. Then, considering the sintering states may be abnormal, a fuzzy relation predictive model based on expert experience is also established. In the end, an integrated predictive model based on the fuzzy T-S predictive model and the fuzzy relation predictive model is presented by combining these two models with a fuzzy classifier. Results of numerical simulation show that the integrated predictive model is more accurate and robust against the uncertainty of vertical burning speed.